Effect of TraN key residues involved in DNA binding on pIP501 transfer rates in Enterococcus faecalis - Michaelis, Claudia; Berger, Tamara M. I.; Kuhlmann, Kirill; Ghulam, Rangina; Petrowitsch, Lukas; Besora Vecino, Maria; Gesslbauer, Bernd; Pavkov-Keller, Tea; Keller, Walter; Grohmann, Elisabeth (Frontiers in Molecular Biosciences, 2024)
Conjugation is one of the major mechanisms facilitating the exchange of antibiotic resistance genes among bacteria. The broad-host-range Inc18 plasmid pIP501 harbors 15 genes encoding for a type IV secretion system (T4SS). It is a membrane-spanning multiprotein complex formed between conjugating donor and recipient cells. The penultimate gene of the pIP501 operon encodes for the cytosolic monomeric protein TraN. TraN acts as a transcriptional regulator by binding upstream of the operon promotor, partially overlapping with the origin of transfer. Additionally, TraN regulates traN and traO expression by binding upstream of the PtraNO promoter. In this study, we investigated the impact of nine TraN amino acids involved in binding to pIP501 DNA through site-directed mutagenesis by exchanging one to three residues by alanine. For three traN variants, complementation of the pIP501∆traN knockout resulted in an increase of the transfer rate by more than 1.5 orders of magnitude compared to complementation of the mutant with native traN. Microscale thermophoresis (MST) was used to assess the binding affinities of three TraN double-substituted variants and one triple-substituted variant to its cognate pIP501 double-stranded DNA. The MST data strongly correlated with the transfer rates obtained by biparental mating assays in Enterococcus faecalis. The TraN variants TraN_R23A-N24A-Q28A, TraN_H82A-R86A and TraN_G100A-K101A not only exhibited significantly lower DNA binding affinities but also, upon complementation of the pIP501∆traN knockout, resulted in the highest pIP501 transfer rates. This confirms the important role of the TraN residues R23, N24, Q28, H82, R86, G100 and K101 in downregulating pIP501 transfer. Although TraN is not part of the mating pair formation complex, TraE, TraF, TraH, TraJ, TraK and TraM were coeluted with TraN in a pull-down. Moreover, TraN homologs are not only present in Inc18 plasmids, but also in RepA_N and Rep_3 family plasmids, which are frequently found in enterococci, streptococci, and staphylococci. This points to a widespread role of this repressor in conjugative plasmid transfer among Firmicutes.